Micro growth of freshwater bivalve (Paxyodon syrmatophorus) with marking fluorochrome calcein - Mara Rúbia Ferreira Barros; Lucas Garcia Martins; Valdo Sena Abreu; Wagner Cesar Rosa dos Santos; Rafael Anaisce das Chagas; Marko Herrmann (PANGAEA, 2020)
Micro growth of freshwater bivalve (Paxyodon syrmatophorus) with marking fluorochrome calcein to validate the assumption of ring formation grown in the Maratauira river, Abaetetuba, Pará